Influence of cue word perceptual information on metamemory accuracy in judgement of learning. Issue 3 (15th March 2016) - Hu, Xiao; Liu, Zhaomin; Li, Tongtong; Luo, Liang
Abstract : Previous studies have suggested that perceptual information regarding to-be-remembered words in the study phase affects the accuracy of judgement of learning (JOL). However, few have investigated whether the perceptual information in the JOL phase influences JOL accuracy. This study examined the influence of cue word perceptual information in the JOL phase on immediate and delayed JOL accuracy through changes in cue word font size. In Experiment 1, large-cue word pairs had significantly higher mean JOL magnitude than small-cue word pairs in immediate JOLs and higher relative accuracy than small-cue pairs in delayed JOLs, but font size had no influence on recall performance. Experiment 2 increased the JOL time, and mean JOL magnitude did not reliably differ for large-cue compared with small-cue pairs in immediate JOLs. However, the influence on relative accuracy still existed in delayed JOLs. Experiment 3 increased the familiarity of small-cue words in the delayed JOL phase by adding a lexical decision task. The results indicated that cue word font size no longer affected relative accuracy in delayed JOLs. The three experiments in our study indicated that the perceptual information regarding cue words in the JOL phase affects immediate and delayed JOLs in different ways.